2017
DOI: 10.1016/j.jcmg.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TCFA on Unanticipated Ischemic Events in Medically Treated Diabetes Mellitus

Abstract: ACS patients with DM and ≥1 TCFA have a high rate of NCL-MACE at 3 years. In contrast, the prognosis of ACS patients with DM but no TCFAs is favorable and similar to patients without DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
2
23
0
2
Order By: Relevance
“…This is important, because DM patients with TCFA have higher occurrence of MACE within 3 years, compared to DM ones without TCFA. Plaque progression in DM patients without TCFA led to similar occurrence of MACE like in non-DM patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because DM patients with TCFA have higher occurrence of MACE within 3 years, compared to DM ones without TCFA. Plaque progression in DM patients without TCFA led to similar occurrence of MACE like in non-DM patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular death, MI, and stroke were less common. Prior studies have demonstrated that long-term adverse outcomes in patients with DM were predominantly caused by new lesions in non-culprit vessels 34. Similarly, untreated OSA was also associated with increased risk of repeat revascularization (mainly in non-target lesions) 35.…”
Section: Discussionmentioning
confidence: 99%
“…In Übereinstimmung mit früheren Beobachtungen aus pathologischen Untersuchungen [13] wurden ähnliche Differenzen der Plaquezusammensetzung zwischen diabetischen und nicht diabetischen Patienten bereits in anderen IVUS-basierten Studien beobachtet [14] und begründen möglicherweise die unterschiedliche klinische Prognose dieser Patientenkollektive. In der Tat waren im IVUS detektierte dünne Deckplatten bei Patienten mit DM mit einer erhöhten Inzidenz an kardiovaskulären Ereignissen in den folgenden 3 Jahren assoziiert [15].…”
Section: Diabetes and Revascularizationunclassified